Study of Indigenous Peoples Institutions in the Implementation of Education Policy in Border Areas in Merauke Regency, South Papua Province - Maturan, Albertus Yosep (KnE Social Sciences, 2025)
This study aims to find out the main duties, functions, and authorities of indigenous institutions in the implementation of border area education policies in Merauke District, South Papua Province. This research was conducted using a qualitative approach. The data sources used are primary and secondary data. The results show that education in the border area of Merauke Regency, especially for people living in local villages, is very far behind due to forestry/foraging habits and the lack of active role of indigenous institutions which have the function of “improving the quality of human resources.” This means that the functions of indigenous institutions related to education have not been fully implemented by the customary institutions. The results also found that the function of the indigenous peoples institution in Merauke district is more concerned with political issues and land buying and selling rather than dealing with educational issues, which are an important factor in the progress of a region, especially in the border area of Merauke Regency. Thus, here the role or function of indigenous peoples institutions in terms of carrying out their functions to encourage the education policy process in the border area of Merauke Regency can run according to expectations.